Determinant Factors Involved In Pregnant Women's Willingness To Receive Covid-19 Vaccine - Risqi Dewi Aisyah; Fitriyani Fitriyani; Dwi Bagus Pambudi (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: The COVID-19 vaccine still has a poor vaccination rate among pregnant women for a variety of reasons, one of which is a lack of knowledge about the vaccine's advantages as well as the potential side effects and risks that may result from the vaccine. The purpose of this research is to discover determinant factors that influence Covid-19 vaccination willingness. Methods: This is a descriptive analytic study with a chronological method. In this study, a total population of 255 pregnant women was sampled, using the first dose of COVID-19 vaccination administered to pregnant women at Kedungwuni II Health Center. This research relies on primary data and a questionnaire that has been assessed for validity and reliability. This study lasted six months, from July to December 2021. The analysis was a multivariate logistic regression analysis. Results: The factors related to the willingness of pregnant women to take part in the COVID-19 vaccination were age (p=0.026), gravida status (p=0.029), ANC frequency (p=0.002) and knowledge about covid 19 vaccination (p=0.001). Conclusion: It is critical for healthcare practitioners to provide information about the COVID -19 vaccination so that expectant mothers do not feel anxious about going to the vaccination sites. Pregnant women should also be informed about the possibility of post-vaccination complications.